STRATEGI DINAS LINGKUNGAN HIDUP KOTA TASIKMALAYA DALAM PENGELOLAAN SAMPAH - Elza Nurul Fadilah; Nurwanda, Asep; Suwarlan, Erlan (Journal of Indonesian Rural and Regional Government, 2025)
Proper waste management is an essential part of maintaining environmental health and the quality of life of the community. Without an adequate management system, waste can cause various problems, ranging from environmental pollution to health problems. Waste management problems in Tasikmalaya City include limited facilities and infrastructure, suboptimal handling, and low public awareness. This study was conducted to identify the strategies implemented by the Environmental Agency in addressing waste management issues. This study used a descriptive method with a qualitative approach. Data were collected through observation and interviews with predetermined informants. The results indicate that the implemented strategies have not been running optimally. Several aspects have shown strategic progress, such as the development of a vision and mission and openness to external collaboration. However, the implementation of the strategies in the field still faces various obstacles, including budget limitations, inadequate facilities, and low public participation. Efforts made by the Agency include submitting additional budgets to the government and utilizing Corporate Social Responsibility (CSR) programs from the private sector to support facility improvements and public education activities. The strategies implemented are still technical in nature and are not supported by a strong institutional and participatory system.